A genome-wide association study identified candidate regions and genes for commercial traits in a Landrace population - Ma, Guojian; Tan, Xihong; Yan, Ying; Zhang, Tianyang; Wang, Jianhua; Chen, Xiaoling; Xu, Jingya (Frontiers in Genetics, 2025)
Backfat thickness (BFT) and feed conversion ratio (FCR) are important commercial traits in the pig industry. With the increasing demand for human health and meat production, identifying functional genomic regions and genes associated with these commercial traits is critical for enhancing production efficiency. In this research, we conducted a genome-wide association study (GWAS) on a Landrace population comprising 4,295 individuals with chip data for BFT and FCR. Our analysis revealed a total of 118 genome-wide significant signals located on chromosomes SSC1, SSC2, SSC7, SSC12, and SSC13, respectively. Furthermore, we identified 10 potential regions associated with the two traits and annotated the genes within these regions. In addition, enrichment analysis was also performed. Notably, candidate genes such as SHANK2, KCNQ1, and ABL1 were found to be associated with BFT, whereas NAP1L4, LSP1, and PPFIA1 genes were related to the FCR. Our findings provide valuable insights into the genetic architecture of these two traits and offer guidance for future pig breeding efforts.